2013
DOI: 10.1021/ie400282q
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Material with Enhanced Contacting Efficiency for Volatile Organic Compound Removal at Ultrashort Contact Time

Abstract: A unique catalyst structure, microfibrous entrapped catalyst (MFEC), was prepared by entrapping support particles (γ-Al2O3, 150–250 μm diam) into metal (Ni-200) microfibers and forming thin flexible sheets. Pleated structures of MFECs containing Pd/γ-Al2O3, Pd–Mn/γ-Al2O3, and Pd–Ce/γ-Al2O3 were investigated systematically for volatile organic compound (VOC) removal at various face velocities (ca. 3–30 m/s) and at low temperatures (<473 K). The optimized structure of MFEC (e.g., W-structure with 8 μm Ni fiber) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The Pd based catalyst operates at a slightly higher range of temperature between 200 and 300 ∘ C as compared to Pt [31][32][33][34]. The oxidation state of Pd influences its catalytic activity and Dégé et al reported that Pd 0 is the active phase and its catalytic performance is highly dependent on its load on supports [31,32].…”
Section: Pd Based Catalystsmentioning
confidence: 99%
“…The Pd based catalyst operates at a slightly higher range of temperature between 200 and 300 ∘ C as compared to Pt [31][32][33][34]. The oxidation state of Pd influences its catalytic activity and Dégé et al reported that Pd 0 is the active phase and its catalytic performance is highly dependent on its load on supports [31,32].…”
Section: Pd Based Catalystsmentioning
confidence: 99%
“…Figure 3 shows the uniquely designed system for testing microfibrous material to achieve catalytic VOC removal at microsecond contact time. 14 The test setup consists of a high pressure 40 hp radial blower (Fan Equipment Company), which circulates air inside the closed-loop system. A variable speed drive is used to control the system speed, which can reach over 30 m/s inlet velocity.…”
Section: Test Setupmentioning
confidence: 99%
“…However, this theoretical investigation required an experimental verification. Therefore, a performance evaluation parameter, heterogeneous contacting efficiency ( η HCE ), was applied to evaluate the performance of those aforementioned reactor geometries . Balakotaiah and West and Giani et al have also considered this parameter for comparing the performance of monolith with packed bed and catalytic foam.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations